(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
this article talks about one of the representatives of the world of fauna - the image of a butterfly. In expressing the artistic landscape of the world, in revealing different aspects of the human image, artists actively use living creatures belonging to the group of animals and insects, among other images. The article expresses an opinion about the genesis of the image of a butterfly, the types of meaning expressed by its first roots. In modern poetry, the role of the image of the butterfly in the composition of the work, its importance, symbolic expressions are explained by giving examples of a number of poetic fragments.